Penilaian Kualitas Daya Sistem Kelistrikan PT. Sai-Pasuruan - Ferdian Ronilaya (Department Industrial Engineering, University of Muhammadiyah Malang, 2007)
The reliability services and power quality of power system nowadays become popular in industry because of cost energy reason, not exception for PT SAI. This company utilize control unit process to produce aluminum foil. The purpose of this research is identifying and analyzing the power quality of PT SAI and then to find the correct and economical solution to extinguish the source of bad power quality. After we identified, we conclude that 65% of load are AC motors, 25% of DC motors, 8% of heater and 2% of lightning. For over voltage and under voltage, refers to IEEE 519 – 1995 standard, PT SAI have 99% of nominal voltage. But for voltage imbalanced, refers to NEMA MG-1-1993 standard, PT SAI have 1,22%. For THD of voltage, PT SAI have 1,98%. But for THD of current, PT SAI have 34,47%. While transformer loading between 0,47% - 29,7%.